Dealing with navigation and interaction requirements changes in a TDD-based web engineering approach - Burella, Juan
Web applications are well suited to be developed with agile methods. However, as they tend to change too fast, special care must be put in change management, both to satisfy customers and reduce developers load. In this paper we discuss how we deal with navigation and interaction requirements changes in a novel test-driven development approach for Web applications. We present it by indicating how it resembles and differs from conventional TDD, and showing how changes can be treated as first class objects, allowing us to automate the application changes and also to adaptively prune the test suite.